PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KANCING GEMERINCING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPS MAN PALANGKI KABUPATEN SIJUNJUNG - Okta Riani, Cherri; Aima, Zulfitri; Haryono, Yulia (Pendidikan Matematika, 2014)
ABSTRACTÂ This research was conducted based on the fact indicating that the students understanding on mathematic concept was still low, the smart students dominate the learning process while the low level of students donât have opportunity to speak and giving argument. The aim of this research was to determine whether students understanding on mathematic concept by implementing cooperative learning technique Button Clatter is better than the students understanding on mathematic concept with conventional learning. This was an experimental research. The sampling technique is total sampling. XI IPS 2 selected as the experimental class andÂ  the class as a class XI IPS 1 control. The instruments of the research was final test study with reliability 0,89. Based on the analysis of date, average valueof the experimental class is 71,82 with standard devition 18,37 and the average value of the control class is 53,82 with standard deviation 21,45. P-Value (0,001) which was smaller than Î±, Thus it was concluded that the studentâs understanding on mathematic concept by implementing cooperative learning technique Button Clatter better then that of the conventional learning in class XI IPS MAN Palangki.